SHIFTS IN TRANSLATION OF NOUN PHRASE FOUND IN THE TEXT CREATURES BEHIND HOUSES - Dewa Made Agustawan (Focus Journal : Language Review, 2022)
This research focuses on the shifts in translation of noun phrase found in the text “Creatures behind Houses”. It aims at describing the types of noun phrase and their translation into Indonesia, investigating and explaining the types of translation procedures that applied. The data were obtained from the bilingual text entitled Creatures behind Houses as the source language. The data were collected by applying the observation method which was supported by implementing note-taking technique in order to find, identify and classify the data. The data were analyzed by applying the qualitative descriptive method in which the noun phrases were presented descriptively along with their descriptions and explanations. There are several theories applied in this research, such as the theory of Indonesian grammar by Sneddon (1996) in order to describe the types of noun phrase and their translation and the theory of translation by Catford (1965) to analyze the types of translation procedures applied. The findings show that there are two types of noun phrases and their translation found in the data. They are level shift, and category shifts which consists of structure shift, unit shifts, and intra-system shifts. Thus there is no class shifts found in the data.